Rehydration on high temperature-mortars based on recycled glass as aggregate. (1st December 2020) - Flores-Alés, V.; Martín-del-Río, J.J.; Alducin-Ochoa, J.M.; Torres-González, M.
Abstract: The incorporation of waste of different nature as components of mortars and cement concretes is a scientifically valid option that allows us to obtain a positive environmental balance in the manufacturing process of these construction materials. Considering the capacity of improvement of the thermal properties provided by glass, this work approaches the recovery by forced rehydration of mortars based on recycled glass after undergoing a process of heating at high temperature. Its mineralogical by XRD, structural evolution by SEM, X-ray computed tomography and DTA/TGA along with its physical-mechanical properties has been analyzed. Results have shown that, although the initial influence of glass can lead to inconsistent results according to the dosage and alteration process suffered, the favourable effect of the crushed glass after a thermal degradation and the subsequent rehydration treatment is observed. The rehydrated material based on recycled glass develops a capacity of mechanical recovery 6.2 times higher than the conventional mortar. This is due to the thermal an alkaline activation of amorphous silica, which favours the new formation of hydrated silicates as manifested the variation of the eccentricity coefficient of the pores: 0.5707 for conventional mortar and 0.6627 for glass based one. Highlights: Incorporation of waste reuse in mortars has a positive environmental impact. Crushed glass aggregates improve the thermal isolate capacity of cement mortars. Glass-based mortars show less degradation due to high temperature action. Thermally activated glass particles react producing new hydrated calcium silicates. Rehydration promotes the recovery of mechanical strength in mortars affected by fire.